Night work and health status of nurses and midwives. cross-sectional study - Burdelak, Weronika; Bukowska, Agnieszka; Krysicka, Jolanta; Pepłońska, Beata (Medycyna pracy, 2012)
The aim of this study was to assess the association between night shift work and the prevalence of diseases and conditions among nurses and midwives. The study included 725 subjects (354 working on night shifts and 371 working only during the day). The data were collected via an interview based on the "Standard Shiftwork Index". We analyzed the frequency of diseases and conditions and the relative risk expressed as the odds ratio (adjusted for important confounding factors). The most common diseases in the study population were chronic back pain (47.2%), hypertension (24.5%) and thyroid diseases (21.2%). We found no statistically significant increased relative risk of any diseases and conditions among the night shift nurses, compared to the day shift ones. The duration of the work performed on night shifts was significantly associated with the relative risk of thyroid diseases--increased almost two times in the women working for 15 or more years in such system (p for trend: 0.031). The analysis showed the significantly increased (more than eight times higher) relative risk of feet swelling in the women with 8 or more night duties per month, compared to the women having fewer night shifts. We did not observe a higher frequency of diseases in the night shift nurses, compared to the day shift nurses. These results may be related to the so-called "Healthy Worker Effect". There is a need for further long-term observational studies in the populations of nurses.